2000
DOI: 10.1111/j.1574-6968.2000.tb09059.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis ofLeptospiraisolates from mainland Portugal and the Azores islands

Abstract: From 228 recent Leptospira isolates from mainland Portugal and Azorean wild mammals, 149 were characterized at the serovar level by monoclonal antibodies (MAbs), a quick serological method in epidemiological studies. In order to compare this antigenic information with that from new genetic techniques, a sample of isolates was analyzed through pulsed-field agarose gel electrophoresis (PFGE) (n=71), mapped restriction site polymorphisms (MRSPs) in PCR-amplified rRNA genes (n=45, including 13 saprophytes) and arb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 18 publications
(31 reference statements)
2
3
0
Order By: Relevance
“…Their reactions to the mAbs specific for the Pomona serogroup were very similar to each other but different from any of the known serogroup Pomona strain profiles. Their pattern was compatible with serovar Tsaratsovo, which was first isolated from harvest mice (Micromys minutus) in 1962, in the Plovdiv District of Bulgaria by Ivanov and later found in rodents in some parts of Europe [66]. Nevertheless, only mAbs F48 C6 and F61 C7, included in our panel, were tested on this serovar.…”
Section: Discussionsupporting
confidence: 64%
“…Their reactions to the mAbs specific for the Pomona serogroup were very similar to each other but different from any of the known serogroup Pomona strain profiles. Their pattern was compatible with serovar Tsaratsovo, which was first isolated from harvest mice (Micromys minutus) in 1962, in the Plovdiv District of Bulgaria by Ivanov and later found in rodents in some parts of Europe [66]. Nevertheless, only mAbs F48 C6 and F61 C7, included in our panel, were tested on this serovar.…”
Section: Discussionsupporting
confidence: 64%
“…Further REA typing of the field strains used in the study showed the same Eco RI and Hha I restriction patterns for all tested isolates, and they were compatible with the DNA profiles of those four very closely related serovars. These results correlated with those of some previous studies, revealing difficulties in genetic discrimination between those strains ( 8 , 17 19 ). Moreover, using monoclonal antibody typing, Kobayashi et al ( 22 , 23 ) also showed a very close antigenic similarity of those strains, which led the authors to put those four serovars in one subgroup.…”
Section: Discussionsupporting
confidence: 91%
“…The MST method permits the strains of the Copenhageni and Icterohaemorrhagiae serovars to be differentiated into five distinct profiles, in contrast to the unique profile by VNTR analysis (18). These two serovars are particularly difficult to discriminate when using other typing methods, such as PFGE (34), VNTR (35), and MLST (36). This MST capacity is particularly interesting for the epidemiologic surveillance of the L. interrogans species carried in rodents, such as Rattus norvegicus, since they are considered the main environmental spreader of zoonotic Leptospira species.…”
Section: Discussionmentioning
confidence: 99%